A Caspase-Independent Pathway Mediates Macrophage Cell Death in Response to Mycobacterium tuberculosis Infection - O'Sullivan, Mary P. (American Society for Microbiology, 2007)
Macrophages can undergo apoptosis after infection with Mycobacterium tuberculosis. This macrophage response deprives the bacillus of its niche cell and supports the host response through better antigen presentation. The intracellular pathways of apoptosis that elaborate this macrophage response are not well understood. To address this issue, we investigated the contribution of various apoptosis pathways to M. tuberculosis-induced macrophage cell death. We found that macrophages die in a caspase-independent manner after infection with M. tuberculosis (at multiplicities of infection ranging from 1 to 20). There was evidence for the involvement of both the mitochondria (cleavage of Bid) and the lysosomes (cathepsin-mediated DNA fragmentation) in this cell death pathway. Dying macrophages displayed several features typical of apoptosis, including DNA fragmentation, nuclear condensation, and exposure of phosphatidylserine on the plasma membrane. However, nuclear fragmentation was not observed, which suggests that M. tuberculosis-induced cell death differs in some respects from classical apoptosis. This novel mechanism of cell death was blocked by serine protease inhibitors. A better understanding of this protective macrophage response may direct new vaccine and treatment options.